Classroom Management through Audiovisual Media in Islamic Elementary Science Learning: Pengelolaan Kelas Melalui Media Audiovisual dalam Pembelajaran Sains di Sekolah Dasar Islam - Fadhilah, Dyah Nur; Arifin, Moch. Bahak Udin By (Indonesian Journal of Islamic Studies, 2025)
General Background: Effective classroom management is a key determinant of successful learning outcomes, particularly in science education, where conceptual understanding often requires interactive methods. Specific Background: At Hasanuddin Islamic Elementary School, integrating audiovisual media into science instruction has been implemented to foster engagement and comprehension among fourth-grade students. Knowledge Gap: However, limited studies have explored how audiovisual-based classroom management specifically shapes students’ participation, discipline, and conceptual grasp in Islamic elementary settings. Aims: This study aims to analyze the implementation and effectiveness of classroom management strategies using audiovisual media in science learning. Results: Findings reveal that audiovisual integration enhances students’ focus, creativity, and motivation while helping teachers maintain class discipline and optimize lesson delivery. Novelty: This research provides insight into the contextual use of audiovisual strategies in Islamic education, combining technological innovation with value-based pedagogy. Implications: The study underscores the need for accessible digital tools in Islamic schools to support dynamic, student-centered learning environments that align with modern educational paradigms. Highlights: Audiovisual media improves classroom dynamics and student participation. Strengthens conceptual understanding through interactive learning. Promotes innovation in Islamic elementary education practices. Keywords: Classroom Anagement, Audiovisual Media, Islamic Education, Science Learning, Student Engagement